2020
DOI: 10.1177/2633105520973985
|View full text |Cite
|
Sign up to set email alerts
|

The First Orally Deliverable Small Molecule for the Treatment of Spinal Muscular Atrophy

Abstract: Spinal muscular atrophy (SMA) is 1 of the leading causes of infant mortality. SMA is mostly caused by low levels of Survival Motor Neuron (SMN) protein due to deletion of or mutation in the SMN1 gene. Its nearly identical copy, SMN2, fails to compensate for the loss of SMN1 due to predominant skipping of exon 7. Correction of SMN2 exon 7 splicing by an antisense oligonucleotide (ASO), nusinersen (Spinraza™), that targets the intronic splicing silencer N1 (ISS-N1) became the first approved therapy for SMA. Rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 147 publications
(210 reference statements)
0
61
0
1
Order By: Relevance
“…Due to upcoming orally available splicing-modulating drugs for SMA, daily medication administration will become possible [ 30 ]. However, some off-target effects were discussed related to risdiplam [ 31 ]. Trials allowing for direct comparisons of intrathecally and orally administered splicing modulators are missing so far.…”
Section: Discussionmentioning
confidence: 99%
“…Due to upcoming orally available splicing-modulating drugs for SMA, daily medication administration will become possible [ 30 ]. However, some off-target effects were discussed related to risdiplam [ 31 ]. Trials allowing for direct comparisons of intrathecally and orally administered splicing modulators are missing so far.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 , 31 ]. Various clinical SMA drug has been approved recent years by the Food and Drug Administration (FDA), such as antisense oligo nucleotides (ASOs) drug Nusinersen (Spinraza) by correction of SMN2 exon 7 splicing, gene therapy targeting SMN1 using AAV [ 31 ], and an orally deliverable small molecule drug-risdiplam (Evrysdi) that the therapeutic effect would be able to reach to all organs [ 32 ]. In this regard, augmenting SMN levels may prove to be a viable strategy to rescue/improve the spermatogenesis efficiencies ex vivo or in vivo for NOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…RNA immunoprecipitation demonstrated that risdiplam analogs preferentially bind to a GA-rich sequence that matched the sequence of exon 7 +22 to +30 [ 28 ]. The analysis of other risdiplam-sensitive genes in splicing demonstrated that the GA-rich sequence was slightly enriched at the 3′ splice site but does not have a strong consensus in all sequences [ 109 , 110 ]. PK4C9 is another small molecule reported as an SMN2 splicing modifier ( Figure 5 b).…”
Section: Known Rna-targeting Splicing Modifiers For the Treatment Of Human Diseasesmentioning
confidence: 99%